Impact of Basel Capital Accord on Bank Behaviour, the impact of Basel Risk based capital requirement (accord I) on Bank performance in the Context of a Small Service-Based island Economy - Ramessur, S.; Polodoo, Viren (Maldives Research, 2015)
This paper tests the effect of the Basel Risk Based Capital Requirements (Basel Accord 1) on Mauritian banks' behaviour, using a sample of 9 commercial banks. In the absence of any simultaneity between change in capital ratio and change in credit risk following the application of 3SLS to an extension of the model proposed by Shrieves and Dahl (1992) , the study applies the Arellano-Bond GMM technique to provide unbiased and more efficient estimates by taking into account dynamic framework. The main result emanating from this research reveals that banks' response to the Basel Risk -Based Capital Accord I requirement, is weak in the Mauritian context and under the period of study.